2002
DOI: 10.1049/ip-rsn:20020531
|View full text |Cite
|
Sign up to set email alerts
|

Constrained filtering method for attitude determination using GPS and gyro

Abstract: I n attitude determination using the unit quaternion representation, the unit norm constraint results in singularity of thc covariancc matrix using classical filtering methods. To cope with this problem, a constrained filtering method is developcd. In this method, the constraint equations and the state equations are trcated as pscudo-iiieasLireiiient equations, so that they can be processed simultaneously with the rcal measurement equations. To illustrate thc application of the proposed scheme, a sccnario usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…where Δ is the sampling, is the process noise, assumed to be Gaussian distributed with zero mean and covariance , and Ξ Ω , accordingly to [16]. The measurement model relates the baselines' coordinates with the quaternion elements estimated by the EKF and the known positions of the GPS antennas in the body fixed frame, accordingly to (23).…”
Section: ) Extended Kalman Filtermentioning
confidence: 99%
See 1 more Smart Citation
“…where Δ is the sampling, is the process noise, assumed to be Gaussian distributed with zero mean and covariance , and Ξ Ω , accordingly to [16]. The measurement model relates the baselines' coordinates with the quaternion elements estimated by the EKF and the known positions of the GPS antennas in the body fixed frame, accordingly to (23).…”
Section: ) Extended Kalman Filtermentioning
confidence: 99%
“…where is the covariance of the angular velocity noise and is the covariance of the angular velocity bias noise, [16]. These two parameters must be tuned in order to obtain the best solution, but since it is not used any rate gyro, it is assumed that the value of is close to zero.…”
Section: (36)mentioning
confidence: 99%
“…As a result, we define H c k,j = ∂h c k ∂x k (x k|k,j−1 ) which gives us a local approximation to the direction of h c k . A stronger form for this solution can be found in past work, 4,5 where R c k will reflect the tightening of the covariance for the state prediction based on the new estimate at each iteration of j. We do not use this form and tighten the covariance matrix within these iterations, since in our form, we can change the number of equality constraints between iterations of j.…”
Section: Nonlinear Equality Constraintsmentioning
confidence: 99%
“…For example, in [2] it is shown that the descriptor dynamics give rise to singular measurement noise covariance, and an extended maximum-likelihood method is applied. This same idea is followed in [3], where the constraint (unit quaternion norm) is treated as a pseudo-measurement. In [4], the error from constraint linearization is treated in a separate step, after the EKF, increasing the computational complexity.…”
Section: Introductionmentioning
confidence: 99%